As exig??ncias do mercado de trabalho para o profissional de inform??tica na cidade de S??o Paulo - Oliveira, Luiz Carlos de (2003)
The objective of this study is identify the profile of technical knowledge necessary for the informatica professional, from research in adds publish on newspapers. The study identify the area of acting profissional, based on research of adds publish on newspapers. The study identify, as well, the profile of the technical knowledge necessary for the informatica professional, for each area of acting profissional. The theoretical substantiate validate this work in three phases: 1. The ???knowledge Society??? and the management of knowledge; 2. The impact of the knowledge in the society and significant changes for the companies and for workers of knowledge; and 3. The education profissional. To approach the use of the potential of new technologies, so much in the development of the new professional competences requested, how much in the functions and profile professional, presents a ???road??? to be followed, plays as a counterpartner to the demands of the labourhand market.